Occupational Stress and Burnout in Educational Administration - Torelli, Joseph A.; Gmelch, Walter H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Stress intrigues and plagues academic and practicing school administrators alike. This paper profiles McGrath's (1976) social-psychological stress process which consists of four stages, and Gmelch's (1988) similar four-stage cycle. A study investigated the relationship between Stage I and Stage IV of the four-stage stress cycle and the influence of an intervening variable, sex roles, on each of the two stages. Three research questions were investigated: (1) To what extent do administrative stress and burnout vary among levels of administration in education? (2) To what extent do administrative stress factors contribute to the dimensions of burnout? and (3) What is the association between sex-role orientation and administrative stress and burnout? Principals and superintendents (N=1,000) in Washington State were randomly selected and stratified to participate in this study. Each was sent the Administrative Work Inventory instrument. Seven hundred and forty administrators responded for a 74 percent return rate. Of the returned surveys, only 655 were fully completed. A variety of qualitative statistical methods were used. Results for each research question are given. Findings include a definite pattern between sex roles and administrator stress and burnout. The androgynous principals and superintendents perceive less stressful situations and burnout than other sex-role classifications. Statistical tables are appended. (Contains 29 references.) (RR)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (San Francisco, CA, April 20-24, 1992).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Burnout; Educational Administration; Elementary Secondary Education; Occupational Surveys; Principals; Sex Role; Stress Variables; Superintendents; Reports, Research; Speeches/Meeting Papers